PENJABARAN NILAI NILAI PANCASILA DALAM PELAKSANAAN PEMILIHAN KEPALA DESA - Samosir, Aquilera Miranda (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Indonesia is a democratic country which means that all its citizens have the same right to vote and village head elections as a means of realizing democracy. This article was conducted with the aim that we describe and find out how the implementation or elaboration of Pancasila values, especially in the implementation of village head elections. The method used in this research is qualitative. Qualitative research is intended to understand the meaning or seek the meaning of events and their connections with ordinary people in certain situations. Basically the power of a democratic country is in the hands of the people for the common good. In Indonesia, the implementation of democracy is based on the Fourth Precept of Pancasila which reads "populist led by expertise in deliberation and representation". Village head elections are one of the manifestations of democracy in Indonesia. Village head elections or often abbreviated as village head elections are the implementation of village leaders in the context of electing village heads who are direct, public, free, confidential, honest and fair. The village head is directly elected by villagers from candidates who meet the village head election requirements and is carried out through the nomination and election stages. Direct election of regional heads is one of the implementations of a democratic system to create a more democratic government. This general election activity has been stipulated in the Pancasila in the fourth Precept, namely democracy led by wisdom and expertise in deliberations and representation. The application of the values of the Fourth Pancasila in the democratic life of Pilkades in Indonesia can be used in prioritizing discussions and making decisions for the common good.